Extensive (pastoralist) cattle contributions to food and nutrition security - Truebswasser, U.; Flintan, Fiona E. (Elsevier, 2019)
This chapter describes how extensive livestock keeping (particularly cattle) contributes to the food and nutrition security of pastoralist communities. A framework of different pathways (production, income, gender and health) is used to consider the different linkages. Challenges related to climate change, conflicts, settlement policies and how they impact diets as well as nutrition outcomes in humans are highlighted.